Association between uric acid and atherosclerosis in community‐dwelling older people: The SONIC study. Issue 1 (9th November 2020) - Tanaka, Kentaro; Kabayama, Mai; Sugimoto, Ken; Akasaka, Hiroshi; Takami, Yoichi; Takeya, Yasushi; Yamamoto, Koichi; Sekiguchi, Toshiaki; Kiyoshige, Eri; Akagi, Yuya; Godai, Kayo; Yasumoto, Saori; et al.
Abstract : Aim: The association between serum uric acid (UA) and atherosclerosis in old people is controversial. Therefore, in this study, we clarified this association by assessing serum UA and common carotid atherosclerosis examined by carotid ultrasound in community‐dwelling older people in their 70s, 80s and 90s in the SONIC study. Methods: A cross‐sectional study was conducted involving 538 men and 577 women recruited from the community. The analysis was performed using serum UA as the explanatory variable and the maximum carotid intima‐media thickness (max‐CIMT) and mean‐IMT as the dependent variables. The analysis was performed by multiple regression using traditional risk factors for atherosclerosis as adjustment variables. Results: Analysis of the association between serum UA and IMT revealed a significant correlation only in women >70 years old. Max‐CIMT (β = 0.081, 95% CI = 0.026, 0.136; P = 0.004) and mean‐IMT (β = 0.015, 95% CI = 0.003, 0.029; P = 0.016) were significant. In the analysis of each age group, a significant correlation was only found in women in their 70s for mean‐IMT (β = 0.031, 95% CI = 0.008, 0.053; P = 0.008). Conclusion: In community‐dwelling women aged about 70 years old, elevated serum UA may be an independent risk factor for IMT thickening as a surrogate marker for atherosclerosis. Geriatr Gerontol Int 2021; 21: 94–101 .